8～64kbit/s super-wideband embedded speech and audio coding algorithm - JIA Mao-shen; BAO Chang-chun; LI Rui (Tongxin xuebao)
Based on the international telecommunication union telecommunication standardization sector （ITU-T） recommendation G.729.1 and modified modulated lapped transform （MLT） coding, a super-wideband embedded variable bit-rate speech and audio coding algorithm was proposed, the bit-rates of this codec was from 8kbit/s to 64kbit/s. The information in the frequencies of 0~7 kHz was encoded by G.729.1 codec at 8~32kbit/s, the information in the frequencies of 7~14 kHz was encoded by the transform coding at 36、40 and 48kbit/s, and G.729.1 residual signal’s MDCT （modified discrete cosine transform） was encoded by the transform coding at 56 and 64kbit/s. The objective and subjective listening tests show that this codec has good performance compared with Terms of Reference given by ITU-T.